Budgeting in Lithuania - Hawkesworth, Ian (OECD Publishing, 2010)
This report covers the budget process in Lithuania. It discusses the four phases in separate sections: budget preparation, legislative approval, budget execution, and accounting and audit. Each section ends with a list of recommendations. The new strategic planning process should strengthen the policy focus of the budget at the level of the line ministries and could be accompanied by a more robust medium.term fiscal framework. All public.private partnerships (PPPs) should be subject to approval by the Ministry of Finance, and municipal use of PPPs should be closely monitored. Parliament operates a well.designed and orderly review process but parliamentary involvement can be further developed. Budget execution is based on sound rules and procedures, and the full development of the programme structure could be accompanied by more flexibility. The shift towards accruals in accounting and financial reporting will enhance transparency and should strengthen fiscal discipline. JEL classification: H610